2009
DOI: 10.1111/j.1365-2265.2008.03394.x
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin is an indicator of insulin resistance in non‐obese prepubertal children born large for gestational age (LGA) and is affected by birth weight

Abstract: LGA children have higher insulin and lower adiponectin levels than AGA children in spite of similar BMI. Adiponectin is a better indicator of insulin resistance in LGA children at prepubertal ages and is affected by birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 38 publications
3
21
0
3
Order By: Relevance
“…Raised concentrations of split proinsulin in adults have been interpreted as evidence of b-cell dysfunction (Temple et al, 1989) and a risk of impaired glucose tolerance (Hales et al, 1991), but its role as a metabolic marker in infancy has remained poorly understood (Hawdon et al, 1993;Singhal et al, 2003). We found a positive association between the high split proinsulin concentration and the ratio of adipocyte-derived cytokines-leptin and adiponectin-which have been found to correlate with adiposity (Schubring et al, 1999;Mantzoros et al, 2009), and metabolic disorders (Valle et al, 2003;Darendeliler et al, 2009) in newborns and children, and, further, to efficaciously reflect cardio-metabolic risks (Steinberger et al, 2003;Norata et al, 2007). On the other hand, weight status at the age of 6 months predicts obesity in childhood (Taveras et al, 2009), and here abdominal obesity, known to impair b-cell function (Hanley et al, 2002), was linked to the high split proinsulin concentration.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Raised concentrations of split proinsulin in adults have been interpreted as evidence of b-cell dysfunction (Temple et al, 1989) and a risk of impaired glucose tolerance (Hales et al, 1991), but its role as a metabolic marker in infancy has remained poorly understood (Hawdon et al, 1993;Singhal et al, 2003). We found a positive association between the high split proinsulin concentration and the ratio of adipocyte-derived cytokines-leptin and adiponectin-which have been found to correlate with adiposity (Schubring et al, 1999;Mantzoros et al, 2009), and metabolic disorders (Valle et al, 2003;Darendeliler et al, 2009) in newborns and children, and, further, to efficaciously reflect cardio-metabolic risks (Steinberger et al, 2003;Norata et al, 2007). On the other hand, weight status at the age of 6 months predicts obesity in childhood (Taveras et al, 2009), and here abdominal obesity, known to impair b-cell function (Hanley et al, 2002), was linked to the high split proinsulin concentration.…”
Section: Discussionsupporting
confidence: 48%
“…The high 32-33 split proinsulin, a well-characterized predictor of insulin resistance in adults and older children (Temple et al, 1989;Mykkanen et al, 1997;Singhal et al, 2003), was taken as a novel marker of adverse metabolic status in infancy. To further investigate the infants' metabolic status and the usefulness of high split proinsulin in its assessment, waist circumference, skinfold thickness and adipocyte-derived cytokines-leptin and adiponectin- (Shea et al, 2003;Valle et al, 2003;Darendeliler et al, 2009;Corvalan et al, 2010) were taken as secondary outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…There are two controversial studies on adiponectin levels in a relatively small number of prepubertal LGA children. One of them showed higher IR and lower adiponectin levels in Turkish nonobese prepubertal LGA than AGA children with similar BMI (37). However, a similar study in Greek prepubertal children found higher adiponectin levels in LGA subjects (38).…”
Section: Discussionmentioning
confidence: 84%
“…71,72 On the other hand, Darendeliler et al have found that LGA children have higher insulin and lower adiponectin levels than AGA children in spite of similar BMI. 73 A study enrolling 52 young adult offspring of obese mothers and 15 offspring of normal weight mothers demonstrated that the former are more likely to be obese and develop insulin resistance than the latter. 74 Of note, higher maternal pre-pregnancy BMI has been associated with higher offspring systolic and diastolic blood pressure, insulin and triglyceride levels and lower HDL cholesterol at 32 years of age.…”
Section: The Influence Of Maternal Obesity On Fetal Development and Imentioning
confidence: 99%